Precipitated silica and its manufacturing method

Integrating alkali metal alkyl siliconates during the silica precipitation process forms methyl groups, addressing the need for enhanced compatibility and heat dissipation in silica-polymer matrices, improving performance in elastomer compositions.

JP7599442B2Active Publication Date: 2024-12-13RHODIA OPERATIONS SAS
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021577035
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-06-27
Filing Date
2020-06-23
Publication Date
2024-12-13
Estimated Expiration
2040-06-23

AI Technical Summary

Technical Problem

Existing methods for chemically modifying precipitated silica to improve compatibility with polymer matrices often require additional steps post-drying, and there is a need for silica with enhanced heat dissipation properties and curing behavior.

Method used

Chemical modification of precipitated silica is integrated into the precipitation process using alkali metal alkyl siliconates, forming methyl groups covalently bonded to silica during the process, resulting in improved heat dissipation and curing properties without subsequent modification steps.

Benefits of technology

The modified silica exhibits enhanced heat dissipation and curing behavior, suitable for use as reinforcing fillers in polymer compositions, particularly in elastomer compositions with reduced rolling resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007599442000001
    Figure 0007599442000001
  • Figure 0007599442000002
    Figure 0007599442000002
  • Figure 0007599442000003
    Figure 0007599442000003
Patent Text Reader

Abstract

Chemically modified precipitated silica characterized by the presence of methyl moieties chemically bonded to the silica and methods for its preparation.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims priority from European Patent Application Publication No. 19305861.7, filed June 27, 2019, the entire contents of which are incorporated herein by reference for all purposes.

[0002] The present invention relates to chemically modified precipitated silica and a method for its preparation. [Background technology]

[0003] The use of precipitated silica as a reinforcing filler in polymer compositions is known.The chemical modification of the surface of precipitated silica with organosilicon compounds is also known to improve the compatibility of precipitated silica with polymer matrices.Generally, chemical modification is carried out on precipitated silica at the end of the silica precipitation process, often as an additional step after drying.

[0004] It has now been found that chemically modified precipitated silicas capable of providing compositions with good heat dissipation properties can be obtained by modification during the silica precipitation reaction by using an alkali metal alkyl siliconate. The presence of an alkali metal alkyl siliconate in the reaction medium during certain stages of the silica precipitation process can form silica chemically modified with alkyl groups. The chemical modification of silica is carried out during the precipitation process without the need for any subsequent modification step.

[0005] The use of alkali metal alkyl siliconates in the preparation of modified precipitated silicas is disclosed, for example, in WO 2018 / 019373, which comprises a compound selected from an acid, a precipitated silica and / or [SiO 4 / 2] A process is disclosed which involves the reaction of a precursor material, as well as an organosilicate, where a modification reaction occurs during or immediately after the reaction to produce precipitated silica. The precipitated silica obtained by this process has a low salt content and finds application as a reinforcing filler in silicone elastomer compositions, toners or developers.

[0006] It has now been found that the precipitation process comprises a step carried out at low pH followed by a step carried out at high pH during which an alkali metal methyl siliconate is added to the reaction medium, and that the resulting precipitated silica is capable of improving the heat dissipation properties of an elastomeric composition and / or its curing behavior, and that tires comprising said elastomeric composition are characterized, inter alia, by reduced rolling resistance. Summary of the Invention

[0007] A first object of the present invention is to provide novel chemically modified precipitated silicas which can be used, for example, as reinforcing fillers in polymer compositions. A second object of the present invention is to provide a process for the preparation of the chemically modified precipitated silicas.

[0008] The precipitated silicas of the invention are characterized, inter alia, by the presence of methyl groups covalently bonded to the silica.The silicas of the invention are defined in detail in the following description and in the claims and examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The precipitated silica of the present invention has the formula [SiO 4 / 2 ] and the formula [(CH 3 )SiO 3 / 2 ] units, which is the unit of precipitated silica 13 It is characterized by the fact that in the C NMR spectrum there are two resonance peaks assigned to methyl groups: the first one in the region from −2.0 to −5.0 ppm and the second one in the region from −5.5 to −9.0 ppm, with the ratio (intensity of the second peak) / (intensity of the first peak) being greater than 0.40.

[0010] The expression "resonance peak between -X and -Y ppm" means that the value of the maximum of the resonance peak is between -X and -Y ppm when the chemical shift scale is calibrated with the adamantane resonance (at 38.5 ppm and 29.4 ppm). 13 It is used herein to indicate presence in the region of the C NMR spectrum.

[0011] It is observed that the resonances assigned to the methyl groups of the silica of the invention are shifted relative to the resonances of the same methyl groups of the alkali metal methyl siliconate used in the preparation of the precipitated silica. For example, if the alkali metal methyl siliconate is potassium methyl siliconate, the single methyl resonance at -1.1 ppm is split into a first peak at -2.0 to -5.5 ppm and a second peak at -5.5 to -9.0 ppm. The first peak may be at -3.0 to -5.0 ppm. The second peak may be at -6.5 to -8.5 ppm.

[0012] The ratio (intensity of the second peak) / (intensity of the first peak) is greater than 0.40. The ratio (intensity of the second peak) / (intensity of the first peak) is preferably 0.45 or more, more preferably 0.50 or more, and even more preferably 0.52 or more.

[0013] The ratio (intensity of the second peak) / (intensity of the first peak) can be as high as 5.00.

[0014] The ratio (intensity of the second peak) / (intensity of the first peak) may be from 0.40 to 5.00, further from 0.45 to 3.00, from 0.45 to 2.00, further from 0.45 to 1.60, or from 0.50 to 1.60.

[0015] The silica of the present invention contains methyl groups chemically bonded to at least a portion of the Si atoms in the silica structure.

[0016] In this specification, the terms "silica" and "precipitated silica" are used synonymously. The expression "precipitated silica" defines an amorphous silica produced by acidification of a solution of sodium silicate, followed by filtration of the precipitate and drying without any step of extracting water from the precipitate using an organic solvent, for example an alcohol or a supercritical fluid.

[0017] The precipitated silica of the present invention has a carbon content of at least 0.2% by weight, typically between 0.2% and 10.0% by weight. Throughout this specification, the carbon content is defined as the amount of carbon by weight relative to the total weight of the silica. The carbon content represents the amount of methyl sites chemically bonded to the precipitated silica. The carbon content is typically less than 10.0% by weight, and it may even be less than 5.0% by weight. Advantageously, the carbon content is between 0.2% and 5.0% by weight, and even between 0.3 and 4.0% by weight. The carbon content may be between 0.2% and 3.5% by weight, and even between 0.3 and 3.0% by weight, and preferably between 0.3 and 2.0% by weight.

[0018] The expressions weight percent and % by weight are used synonymously.

[0019] Generally, the precipitated silica according to the invention has a melting point of 40 to 600 m 2 / g. The CTAB surface area is at least 50 m 2 / g, at least 60m 2 / g, at least 80m 2 / g, and at least 120m 2 / g, at least 160m 2 / g, at least 205m 2 / g, at least 210m 2 / g. The specific surface area of ​​CTAB can be up to 450 m 2 / g, up to 380m 2 / g, and up to 300m 2 The CTAB surface area can be in particular between 50 and 450 m 2 / g, especially 60-380m 2 / g, e.g. 80~300m 2 / g.

[0020] In one embodiment, the precipitated silica of the present invention is - 40m 2 / g~600m 2 / g, preferably 50m 2 / g~380m 2 / g, more preferably 60m 2 / g~300m 2 / g CTAB surface area, and - a carbon content of 0.2% to 3.5% by weight, preferably 0.3% to 3.0% by weight It is characterized by:

[0021] A further feature of the silicas of the invention is their large median particle size (particle diameter) d50 for a given CTAB surface area value. In particular, it has been found that the median particle size of the silicas of the invention at a given CTAB surface area is larger than that measured for known organically modified precipitated silicas.

[0022] The median particle size d50 and CTAB surface area of ​​the silica of the present invention are: |d50|>164.5-0.3×|CTAB| (I) It was found that the .alpha.-methyl-.alpha.

[0023] In formula (I), |CTAB| is m 2 This is the numerical value of the CTAB surface area expressed in g / g. |CTAB| is a dimensionless number. For example, if the measured CTAB is 200 m 2 / g, |CTAB| is 200.

[0024] In formula (I), |d50| represents the numerical value of the median particle size d50 measured by centrifugal sedimentation and expressed in nm. For example, if the value of d50 measured by centrifugal sedimentation is 100 nm, |d50| is 100. d50 represents the diameter below (and above) which 50% of the total mass of the aggregates is found. Thus, d50 represents the median particle size of a given distribution, and in this context, the term "size" shall mean "diameter". |d50| is a dimensionless number.

[0025] The precipitated silica according to the present invention is typically 45 ml 2 / g~650m 2 / g, especially 70m 2 / g~500m 2 / g, and further 90~400m 2 / g, e.g. 90~370m 2 / g. The BET surface area can be determined according to the Brunauer-Emmett-Teller method detailed in standard NF ISO 5794-1, Appendix E (June 2010).

[0026] The precipitated silica according to the invention has a maximum viscosity of 0.50 g / cm3, measured according to standard ISO 787 / 11. 3 , preferably 0.15 to 0.50 g / cm 3 , especially 0.15 to 0.40 g / cm 3 has a packing density of

[0027] The precipitated silica of the invention can be advantageously obtained by a process comprising the reaction of a silicate with an acid to produce a suspension of precipitated silica, said reaction comprising at least one step in which at least one alkali metal methyl siliconate is provided to the reaction medium after 50% of the precipitation reaction has taken place.

[0028] A second object of the present invention is therefore a process for preparing the precipitated silica of the present invention.

[0029] The term "silicate" is used herein to refer to one or more silicates that may be added during the course of the method of the present invention. The term "silicate" is used herein to refer to a compound selected from the group consisting of alkali metal silicates. Advantageously, the silicate is selected from the group consisting of sodium silicate and potassium silicate. The silicate may be in any known form, such as metasilicate or disilicate.

[0030] If sodium silicate is used, the latter generally has a SiO of 2.0 to 4.0, in particular 2.4 to 3.9, for example 3.1 to 3.8. 2 / Na 2 O weight ratio.

[0031] Generally, the silicate is provided as a solution having a concentration of typically 3.9% to 25.0% by weight, for example 5.6% to 23.0% by weight, in particular 5.6% to 20.7% by weight. Throughout this specification, the silicate concentration in the solution is referred to as SiO 2 It is expressed as weight.

[0032] The term "acid" is used herein to refer to one or more acids that may be added during the course of the method of the present invention. Any acid may be used in the process. Generally, mineral acids such as sulfuric acid, nitric acid, or hydrochloric acid, or organic acids such as acetic acid, formic acid, or carbonic acid are used. Sulfuric acid is preferred.

[0033] The acid may be metered into the reaction medium in dilute or concentrated form. Different concentrations of the same acid may be used at different stages of the process.

[0034] In a preferred embodiment of the process, sulfuric acid and sodium silicate are used at all stages of the process.

[0035] The process of the invention is characterized by the fact that at least one alkali metal methyl siliconate is added to the reaction medium after 50% of the precipitation reaction has taken place.

[0036] The expression "after 50% of the precipitation reaction has occurred" is used herein to mean the SiO 2 produced up to said given stage. 2 The amount of SiO produced in this process 2 It is used to indicate any stage in a process in which the total amount of

[0037] Depending on the process, the rate of silica precipitation can be monitored in various ways. In one variant of the process, the formation of 50% by weight of the total amount of silica corresponds to the addition to the reaction medium of 50% of the total amount of silicate added during the process.

[0038] In another variation, when the neutralization rate of the reaction medium reaches 50%, the formation of 50% by weight of the total amount of silica is achieved. The term "neutralization ratio" refers to the ratio of the H produced by the acid added to the reaction medium. + to the number of moles of alkali metal derived from silicate in the reaction medium.

[0039] Notable examples of suitable alkali metal methyl siliconates include those represented by the general formula (II): HO-[Si(CH 3 )(OM)-O-] n H (II) or (III): (CH 3 ) 2 Si(OM) 2 (wherein n is an integer from 1 to 6, particularly from 1 to 3, preferably 1, and M is an alkali metal, preferably sodium or potassium.) It is of the following.

[0040] Preferably, the alkali metal methyl siliconate is selected from sodium or potassium methyl siliconate.

[0041] The method of the present invention comprises the steps of: (i) providing a starting solution having a pH of 2.0 to 5.0, preferably 2.5 to 5.0; (ii) adding silicate and acid simultaneously to the starting solution, whereby the pH of the resulting reaction medium is maintained between 2.0 and 5.0; (iii) stopping the addition of acid while continuing the addition of silicate to the reaction medium until a pH value of the reaction medium between 7.0 and 10.0 is obtained; (iv) adding simultaneously a silicate and an acid to the reaction medium obtained in (iii), whereby the pH is maintained between 7.0 and 10.0; (v) stopping the addition of silicate while continuing the addition of acid to the reaction medium until a pH value of the reaction medium of less than 6.0 is reached and a silica suspension is obtained. characterised in that in step (iv) or (v) at least one alkali metal methyl siliconate is metered into the reaction medium.

[0042] The addition of the alkali metal methyl siliconate is carried out after 50% of the total amount of silicate has been added to the reaction medium. The total amount of silicate to obtain a given final amount of silica can be determined by the person skilled in the art at the beginning of the process according to common general knowledge.

[0043] In a first embodiment of the process, the entire addition of the alkali metal methyl siliconate is carried out during step (iv).

[0044] In a second embodiment of the process, the entire addition of the alkali metal methyl siliconate is carried out during step (v).

[0045] In a first aspect of said embodiment, step (v) comprises two stages, a first stage in which the acid and the alkali metal methyl siliconate are metered simultaneously into the reaction medium at a pH of between 7.0 and 10.0, followed by a second stage in which the addition of the alkali metal methyl siliconate is stopped while the addition of the acid is continued and the pH of the reaction medium is lowered to below 6.0.

[0046] The process may include additional steps, particularly where the pH is further varied by the addition of silicates and / or acids to the reaction medium.

[0047] Without wishing to be bound by theory, it is believed that combining the addition of the alkali metal methyl siliconate with the first precipitation step, carried out at a pH of 2.5-5.0 after 50% of the precipitation reaction has occurred, allows for the incorporation of the methyl moieties of the alkali metal alkyl siliconate in different parts of the structure of the precipitated silica, as evidenced by the presence of different methyl groups in the NMR spectrum of the product.

[0048] In all process embodiments outlined above, regardless of the stage of addition of at least one alkali metal methyl siliconate, the cumulative amount of said compound metered into the reaction medium is at least 0.5% by weight, typically at least 1.0% by weight, or even at least 5.0% by weight. The total amount of at least one alkali metal methyl siliconate is typically not more than 10.0% by weight. Suitable ranges are generally 1.0-10.0% by weight, 2.0-10.0% by weight, or even 2.0-8.0% by weight. The amount of alkali metal methyl siliconate is calculated relative to the silica concentration in the starting solution (calculated as the sum of the initial amount of silicate and the initial amount of alkali metal methyl siliconate).

[0049] The cumulative amount of said compounds metered into the reaction medium is such that the carbon content of the precipitated silica is at least 0.2% by weight, typically 0.2-10.0% by weight. The rate of addition of the alkali metal methyl siliconate can be adapted by means known to those skilled in the art to obtain the desired content of methyl sites in the precipitated silica.

[0050] The reaction vessel in which the entire reaction between the silicate and the acid is carried out is usually equipped with suitable stirring and heating devices.

[0051] The overall reaction of the silicate with the acid is generally carried out at a temperature between 40 and 96° C., in particular between 80 and 95° C. According to one variant of the invention, the overall reaction of the silicate with the acid is generally carried out at a constant temperature between 40 and 96° C., in particular between 80 and 95° C.

[0052] According to another variant of the invention, the temperature at the end of the reaction is higher than the temperature at the beginning of the reaction, which is therefore preferably kept at 40-80° C., then the temperature is preferably increased to a value of 80-96° C. and maintained at that value until the end of the reaction.

[0053] At the end of the steps just described for each of the process embodiments, a suspension of precipitated silica is obtained, which is then subjected to a separation step (liquid / solid separation).The process in all of its embodiments therefore typically includes the further steps of filtering the suspension of precipitated silica and drying the precipitated silica.This process does not include a step of extracting water from the precipitate using an organic solvent, such as an alcohol or a supercritical fluid.

[0054] This separation usually involves filtration followed, if necessary, by washing, which filtration is carried out according to any suitable method, for example by means of a belt filter, a rotary filter, for example a vacuum filter or preferably a filter press.

[0055] The filter cake is then subjected to a liquefaction operation. The term "liquefaction" is intended herein to indicate the process of converting a solid, i.e., the filter cake, into a fluid-like mass. After the liquefaction step, the filter cake is in a flowable, fluid-like form and the precipitated silica is in suspension.

[0056] The liquefaction step may include a mechanical treatment that results in a reduction in the particle size distribution of the suspended silica. Said mechanical treatment may be carried out by passing the filter cake through a high shear mixer, a colloid type mill or a ball mill. Optionally, the liquefaction step may be carried out by subjecting the filter cake to chemical action, for example by adding water or an acid. Both mechanical and chemical treatments may be carried out. The suspension of precipitated silica obtained after the liquefaction step is then dried.

[0057] Drying can be carried out according to techniques known in the art. Preferably, drying is carried out by spraying. For this purpose, any type of suitable sprayer can be used, in particular turbine, nozzle, liquid pressure or two-fluid spray dryers.

[0058] If the drying operation is carried out using a nozzle spray dryer, the precipitated silica obtained is usually in the form of substantially spherical beads. After this drying operation, the recovered product can optionally be subjected to a grinding or pulverization step, and the precipitated silica obtained is generally in the form of a powder.

[0059] Finally, the product dried, ground or pulverized as indicated above may optionally be subjected to an agglomeration step, consisting for example of direct compression, wet granulation (i.e. using a binder such as water, a silica suspension, etc.), extrusion or preferably dry compaction. The precipitated silicas obtainable by this agglomeration step are generally in the form of granules.

[0060] The precipitated silica of the present invention can be used in many applications, such as the manufacture of thermal insulation materials. The precipitated silica of the present invention can also be used as an absorbent or as an additive in concrete or paper, in the preparation of resorcinol-formaldehyde / silica composites.

[0061] The precipitated silicas of the present invention may find particularly advantageous use as fillers in polymer compositions.

[0062] A further object of the present invention is therefore a composition comprising the precipitated silica of the present invention. The composition advantageously comprises the precipitated silica of the present invention and at least one polymer. The at least one polymer may be chosen from among thermosetting polymers and thermoplastic polymers. Notable non-limiting examples of thermosetting polymers include thermosetting resins such as epoxy resins, unsaturated polyester resins, vinyl ester resins, phenolic resins, epoxy acrylate resins, urethane acrylate resins, phenoxy resins, alkyd resins, urethane resins, maleimide resins and cyanate resins.

[0063] Notable non-limiting examples of suitable thermoplastic polymers include polystyrene, (meth)acrylic acid ester / styrene copolymers, acrylonitrile / styrene copolymers, styrene / maleic anhydride copolymers, styrenic polymers such as ABS, ASA and AES, acrylic polymers such as polymethyl methacrylate, polycarbonates, polyamides, polyesters such as polyethylene terephthalate and polybutylene terephthalate, polyphenylene ethers, polysulfones, polyaryletherketones, polyphenylene sulfides, thermoplastic polyurethanes, polyolefins such as polyethylene, polypropylene, polybutene, poly-4-methylpentene, ethylene / propylene copolymers, ethylene / α-olefin copolymers, copolymers of α-olefins with various monomers such as ethylene / vinyl acetate copolymers, ethylene / (meth)acrylic acid ester copolymers, ethylene / maleic anhydride copolymers, ethylene / acrylic acid copolymers, aliphatic polyesters such as polylactic acid, polycaprolactone and aliphatic glycol / aliphatic dicarboxylic acid copolymers.

[0064] The silica of the invention can be advantageously used as a reinforcing filler in elastomer compositions. A preferred object of the invention is therefore a composition comprising the silica of the invention and one or more elastomers. The elastomers preferably exhibit at least one glass transition temperature between -150°C and +300°C, for example between -150°C and +20°C.

[0065] For example, elastomers derived from aliphatic or aromatic monomers containing at least one unsaturation, such as ethylene, propylene, butadiene, isoprene, styrene, acrylonitrile, isobutylene or vinyl acetate, polybutyl acrylate or mixtures thereof, among others, may be used. Mention may also be made of functionalized elastomers, which are elastomers functionalized by chemical groups located along the polymer chain and / or at one or more of its ends (for example by functional groups capable of reacting with the surface of the silica) and halogenated polymers.

[0066] Notable but non-limiting examples of suitable elastomers are diene elastomers. Among diene elastomers, mention may be made for example of polybutadiene (BR), polyisoprene (IR), butadiene copolymer, isoprene copolymer or mixtures thereof, in particular styrene / butadiene copolymer (SBR, in particular ESBR (emulsion) or SSBR (solution)), isoprene / butadiene copolymer (BIR), isoprene / styrene copolymer (SIR), isoprene / butadiene / styrene copolymer (SBIR), ethylene / propylene / diene terpolymer (EPDM) and also related functionalized polymers (presenting pendant polar groups or polar groups at chain ends, for example, capable of interacting with silica).

[0067] Mention may also be made of natural rubber (NR) and epoxidized natural rubber (ENR).

[0068] The polymeric compositions may be sulfur vulcanized or crosslinked, among others, with peroxides or other crosslinking systems, such as diamines or phenolic resins.

[0069] Generally, the polymer composition further comprises at least one (silica / polymer) coupling agent and / or at least one coating agent, which may further comprise, inter alia, an antioxidant.

[0070] Notable non-limiting examples of coupling agents include, for example, "symmetric" or "asymmetric" silane polysulfides, more specifically bis((C1-C4)alkoxyl(C1-C4)alkylsilyl(C1-C4)alkyl) polysulfides (specifically disulfides, trisulfides or tetrasulfides), such as bis(3-(triethoxysilyl)propyl) polysulfides, such as bis(3-(trimethoxysilyl)propyl) polysulfide or triethoxysilylpropyl tetrasulfide. Also included are monoethoxydimethylsilylpropyl tetrasulfides. Also included are silanes containing masked or free thiol or thioester functions, such as 3-octanoylthio-1-propyltriethoxysilane.

[0071] The weight ratio of the silica of the invention in the polymer composition can vary within a fairly wide range. The weight ratio usually represents from 10% to 200%, in particular from 20% to 160%, of the weight of the polymer. In one embodiment, the precipitated silica of the invention may represent from 20% to 80%, for example from 30% to 70%, of the weight of the polymer. In an alternative embodiment, it may represent from 80% to 140%, for example from 90% to 120%, of the weight of the polymer.

[0072] A particular object of the present invention is a composition comprising the precipitated silica of the present invention, typically in an amount between 20% and 160% by weight of the polymer, and at least one polymer selected from the group consisting of diene elastomers, natural rubber and epoxidized natural rubber as detailed above.

[0073] The silica according to the invention may advantageously constitute all of the reinforcing inorganic filler and even all of the reinforcing filler of the polymer composition.

[0074] The composition comprising the precipitated silica of the present invention can be used for the manufacture of many articles.Non-limiting examples of the finished products comprising the precipitated silica of the present invention and the above-mentioned composition are, for example, shoe soles, flooring, gas barriers, flame retardant materials, and also engineering parts, such as rollers for cableways, seals for household appliances, seals for liquid or gas pipes, brake system seals, pipes (flexible), sheathing (especially cable sheathing), cables, engine supports, battery separators, conveyor belts or transmission belts, etc.The composition of the present invention can be advantageously used in the manufacture of tires and tire parts.

[0075] A further object of the invention is a tire or tire component comprising the precipitated silica of the invention.

[0076] To the extent that the disclosure of any patents, patent applications, and publications incorporated herein by reference conflicts with the statements of this application to the extent that the term may be unclear, the statements of this application shall control.

[0077] The present invention will now be described with reference to the following examples, the purposes of which are merely illustrative and are not intended to limit the scope of the invention. EXAMPLES

[0078] Analysis method The physicochemical properties of the precipitated silica of the invention were determined using the methods described below.

[0079] CTAB surface area The CTAB surface area was determined according to standard NF ISO 5794-1, Appendix G (June 2010).

[0080] Determination of total carbon content The total carbon content was measured using a carbon / sulfur analyzer such as the Horiba EMIA 320 V2. The principle of the carbon / sulfur analyzer is based on the combustion of a solid sample in a flow of oxygen in an induction furnace (tuned to about 170 mA) in the presence of a combustion promoter (about 2 g of tungsten (specifically Lecocel 763-266), about 1 g of iron and about 0.25 g of tin). The carbon present in the sample to be analyzed (weight about 0.2 g) combines with oxygen to produce CO 2 , forming CO. These gases are then analyzed by an infrared detector. Moisture from the sample and water produced during these oxidation reactions is removed by passing it over a cartridge containing a dehydrating agent (magnesium perchlorate) so as not to interfere with the infrared measurement.

[0081] The results are expressed as the weight percent of elemental carbon relative to the total weight of the silica sample.

[0082] 13 C NMR spectroscopy The products were analyzed by 1D spectroscopy on a Bruker Avance Solid State 300 spectrometer operating at 7.04 T. 13 The compounds were characterized by C MAS NMR spectroscopy. A commercial 4 mm high-speed probe (DVT4) with a spinning frequency of 10 KHz was used, with cross-polarization by 90° pulses, 3 ms contact time and 5 s recycle time, and 10,000-20,000 transients. The region of the spectrum analyzed for identification of methyl resonances was from -15 to 10 ppm.

[0083] Calibration was performed against adamantane, which is characterized by two chemical shifts at 38.5 ppm and 29.4 ppm.

[0084] Data analysis was performed using the built-in TOPSPIN 4.0.6 software. The most intense signals in the spectra from -2.0 to -5.0 ppm and -5.5 to -9.0 ppm were manually selected, and the intensity of each peak was determined.

[0085] BET surface area determination The BET surface area was determined according to the Brunauer-Emmett-Teller method detailed in standard NF ISO 5794-1, Appendix E (June 2010), with the following adjustments: the samples were pre-dried at 200 °C ± 10 °C and the partial pressure P / P used for the measurements was 0 was in the range of 0.05 to 0.3.

[0086] Determination of particle size distribution and particle size by centrifugal sedimentation in a disc centrifuge (CPS) The d50 values ​​were determined by centrifugal sedimentation in a disk centrifuge using a centrifugal photosedimentometer type "CPS DC 24000UHR" sold by CPS Instruments, Inc. The instrument is equipped with operating software supplied with the device (operating software version 11g).

[0087] The same method and the same tools as described in WO 2018 / 202752A1 (paragraphs

[0155] to

[0178] ) were used to determine the d50 of the silica of the present invention.

[0088] Example 1 In a 25 L stainless steel reactor, add 16.7 L of purified water, 260.2 g of Na 2 SO 4 (solid) was introduced. The solution was stirred and heated to reach 92° C. All reactions were carried out at this temperature. A 7.7% by weight solution of sulfuric acid was metered into the reactor until the pH of the medium reached a value of 3.8.

[0089] Then, sodium silicate solution (SiO 2 / Na 2 O ratio=3.46, SiO 2 Concentration = 19.5% by weight, used during the entire process) was introduced simultaneously with a 7.7% by weight sulfuric acid solution at a flow rate of 112 g / min for 15 minutes. The flow rate of the sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 4.1. After this step, the sodium silicate solution was introduced at the same flow rate for another 10 minutes, keeping the pH constant at 4.1 using 95% by weight sulfuric acid.

[0090] The introduction of acid was stopped, while the addition of silicate was maintained at a flow rate of 123 g / min, until the reaction medium reached a pH value of 8.0.

[0091] At the same time, sodium silicate and 95% by weight sulfuric acid solution were metered into the reactor at a flow rate of 178 g / min over a period of 8 minutes. The flow rate of the sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 8.0. Then, 331 g of potassium methylsiliconate solution (SILRES® BS 16, Wacker Chemie AG, 50% by weight) was metered into the reaction medium over a period of 10 minutes while keeping the flow rate of sodium silicate constant. The pH was maintained at a pH of 8.0 using 95% by weight sulfuric acid.

[0092] At the end of the simultaneous addition, the pH of the reaction medium was brought to 4.8 with sulfuric acid 95% by weight. The reaction mixture was left for 5 minutes.

[0093] The silica suspension thus obtained was filtered and washed with a filter press. The filter cake thus obtained was mechanically disintegrated by adding water to a solids content of 15.4% by weight. The pH of the silica suspension thus obtained was brought to 6.2 by adding a 7.7% by weight sulfuric acid solution. The suspension thus obtained was dried by a nozzle spray dryer to obtain precipitated silica S1. The characteristics of precipitated silica S1 are reported in Table 1.

[0094] Example 2 In a 25 L stainless steel reactor, 15.7 L of purified water and 244.4 g of Na 2 SO 4 (solid) was introduced. The solution was stirred and heated to reach 92° C. All reactions were carried out at this temperature. A 7.7% by weight solution of sulfuric acid was metered into the reactor until the pH of the medium reached a value of 3.8.

[0095] Then, sodium silicate solution (SiO 2 / Na 2 O ratio=3.46, SiO 2Concentration = 19.5% by weight, used during the entire process) was introduced simultaneously with a 7.7% by weight sulfuric acid solution at a flow rate of 105 g / min for 15 minutes. The flow rate of the sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 4.1. After this step, the sodium silicate solution was introduced at the same flow rate for another 10 minutes, keeping the pH constant at 4.1 using 95% by weight sulfuric acid.

[0096] The introduction of acid was stopped, while the addition of silicate was maintained at a flow rate of 123 g / min, until the reaction medium reached a pH value of 8.0.

[0097] At the same time, sodium silicate and 95% by weight sulfuric acid solutions were metered in at a flow rate of 167 g / min over a period of 18 minutes. The flow rate of the sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 8.0. Then, 368 g of potassium methylsiliconate solution (SILRES® BS 16, Wacker Chemie AG, 50% by weight) were metered into the reaction medium over a period of 10 minutes. The pH was maintained at a pH value of 8.0 using 95% by weight sulfuric acid.

[0098] At the end of the simultaneous addition, the pH of the reaction medium was brought to 4.8 with sulfuric acid 95% by weight. The reaction mixture was left for 5 minutes.

[0099] The silica suspension thus obtained was filtered and washed with a filter press. The filter cake thus obtained was washed with a sodium aluminate solution (Al 2 O 3 Concentration: 12% by weight) was added and mechanically decomposed to obtain 3000 ppm Al / SiO 2 The pH of the silica suspension obtained was brought to 6.2 by adding a 7.7% by weight solution of sulfuric acid. The suspension obtained was dried by a nozzle spray dryer to obtain precipitated silica S2. The characteristics of precipitated silica S2 are reported in Table 1.

[0100] Example 3 In a 25 L stainless steel reactor, 16.7 L of purified water and 260.2 g of Na 2 SO 4(solid) was introduced. The solution was stirred and heated to reach 92° C. All reactions were carried out at this temperature. A 7.7% by weight solution of sulfuric acid was metered into the reactor until the pH of the medium reached a value of 3.8.

[0101] Then, sodium silicate solution (SiO 2 / Na 2 O ratio=3.46, SiO 2 Concentration = 19.5% by weight, used in the entire process) was introduced simultaneously with a 7.7% by weight sulfuric acid solution at a flow rate of 112 g / min for 15 minutes. The flow rate of the sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 4.1. After this step, the sodium silicate solution was introduced at the same flow rate for another 10 minutes, keeping the pH constant at 4.1 using 95% by weight sulfuric acid.

[0102] The introduction of acid was stopped, while the addition of silicate was maintained at a flow rate of 123 g / min, until the reaction medium reached a pH value of 8.0.

[0103] At the same time, sodium silicate and 95% by weight sulfuric acid solutions were metered in at a flow rate of 178 g / min over a period of 8 minutes. The flow rate of the sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 8.0. Then, 993 g of potassium methylsiliconate solution (SILRES® BS 16, Wacker Chemie AG, 50% by weight) were metered into the reaction medium over a period of 10 minutes while keeping the flow rate of sodium silicate constant. The pH was maintained at a value of 8.0 using 95% by weight sulfuric acid.

[0104] At the end of the simultaneous addition, the pH of the reaction medium was brought to 4.8 with sulfuric acid 95% by weight. The reaction mixture was left for 5 minutes.

[0105] The silica suspension thus obtained was filtered and washed with a filter press. The filter cake thus obtained was mechanically disintegrated by adding water to reach a solids content of 15.4% by weight. The pH of the silica suspension obtained was brought to 6.2 by adding a 7.7% by weight solution of sulfuric acid. The suspension obtained was dried by a nozzle spray dryer to obtain precipitated silica S3. The characteristics of precipitated silica S3 are reported in Table 1.

[0106] [Table 1]

[0107] Comparative Silica CS1: A sample of Zeosil® Premium 200MP (available from Solvay SA).

[0108] Example 4 - Comparative Example 1 Silica S1 was evaluated in an SBR / BR matrix, the compositions expressed as parts by weight per 100 parts of elastomer (phr) being given in Table 2 below.

[0109] [Table 2]

[0110] The preparation process of the rubber composition was carried out in two successive preparation stages: a first stage of high-temperature thermomechanical processing, followed by a second stage of mechanical processing at a temperature below 110°C to introduce the vulcanization system.

[0111] The first stage was carried out using a mixing device of the Brabender brand internal mixer type (volume of 380 mL). In the first pass of the first stage, the elastomer and reinforcing filler (introduced in portions) were mixed with the coupling agent, resin, DPG and stearic acid. The duration was about 3-4 minutes 30 seconds and the drop temperature was about 140-150°C. After cooling the mixture (temperature below 100°C), a second pass was carried out to incorporate zinc oxide and protective agents / antioxidants and to allow the silanization to continue. The duration of this pass was 4 minutes and the drop temperature was about 150-160°C.

[0112] After cooling the mixture (temperature below 100° C.), the vulcanization system (sulfur and accelerator, e.g. CBS) was added during a second stage, which was carried out on an open mill preheated to 50° C. The duration of this stage was 2 to 6 minutes. Each final mixture was then calendered into plaques of thickness 2 to 3 mm.

[0113] Mechanical properties of vulcanizates Measurements were carried out on vulcanized compositions cured at 160° C. for 1 hour.

[0114] Shore A hardness measurements of the vulcanizates were performed according to standard ASTM D 2240. The values ​​given were measured in 3 seconds.

[0115] Uniaxial tensile tests were carried out with type H2 test specimens in an Instron 5564 machine at a speed of 500 mm / min according to the instructions of standard NF ISO 37. The x% modulus and tensile strength corresponding to the stress measured at x% of tensile strain are expressed in MPa and the elongation at break is expressed in MPa.

[0116] The values ​​of the loss factor (tan δ) and the amplitude of the elastic modulus in dynamic shear (ΔG') were measured for vulcanized samples (8 mm cross section). 2The strain amplitude sweep process was performed following a forward-return cycle going outwards from 0.1% to 50% and then back from 50% to 0.1%. The values ​​reported in Table 3 are obtained from the return strain amplitude scan and relate to the maximum value of the loss factor (tan δmax).

[0117] [Table 3]

[0118] Compositions containing the silica of the present invention exhibit significantly reduced energy dissipation values ​​(ΔG′ and tan δmax) and similar mechanical properties relative to compositions containing precipitated silica according to the prior art.

Claims

1. Formula [SiO 4/2 ] and the formula [(CH 3 ) SiO 3/2 and wherein the precipitated silica comprises units of 13 1. A precipitated silica characterized in that it exhibits in its C NMR spectrum two resonance peaks assigned to methyl groups: a first one in the region from −2.0 to −5.0 ppm and a second one in the region from −5.5 to −9.0 ppm, and a ratio (intensity of the second peak) / (intensity of the first peak) greater than 0.

40.

2. 2. A precipitated silica according to claim 1, wherein said ratio (intensity of the second peak) / (intensity of the first peak) is between 0.50 and 1.

60.

3. 3. Precipitated silica according to claim 1, having a carbon content ranging from 0.2% to 10.0% by weight relative to the total weight of the silica.

4. 40 to 600 m 2 4. Precipitated silica according to claim 1, characterized by a CTAB surface area in the range of 0.1 to 0.5 nm / g.

5. 50m 2 / g~380m 2 5. Precipitated silica according to claim 1, characterized by a CTAB surface area of ​​0.1 to 1.0 nm / g and a carbon content of 0.2% to 3.5% by weight.

6. The median particle size d50 and CTAB surface area of ​​the precipitated silica are |d50|>164.5-0.3×|CTAB| (Wherein, |CTAB| is m 2 / g and |d50| represents the value of the median particle size d50 measured by centrifugal sedimentation and expressed in nm).

6. Precipitated silica according to claim 1, characterized in that it is

7. A process for preparing the precipitated silica according to any one of claims 1 to 6, comprising the steps of (i) providing a starting solution having a pH of 2.0 to 5.0; (ii) adding silicate and acid simultaneously to the starting solution, whereby the pH of the resulting reaction medium is maintained between 2.0 and 5.0; (iii) stopping the addition of acid while continuing the addition of silicate to the reaction medium until a pH value of the reaction medium between 7.0 and 10.0 is obtained; (iv) adding simultaneously a silicate and an acid to the reaction medium obtained in (iii), whereby the pH is maintained between 7.0 and 10.0; (v) stopping the addition of silicate while continuing the addition of acid to the reaction medium until a pH value of the reaction medium of less than 6.0 is reached and a silica suspension is obtained; in which in step (iv) or (v) at least one alkali metal methyl siliconate is added to the reaction medium, and after 50% of the precipitation reaction has taken place a first precipitation stage carried out at a pH of 2.5 to 5.0 is combined with the addition of an alkali metal methyl siliconate, the total amount of the at least one alkali metal methyl siliconate being 1.0 to 10.0% by weight, the amount of the alkali metal methyl siliconate being calculated on the sum of the initial amount of silicate and the initial amount of the alkali metal methyl siliconate.

8. 8. The method of claim 7, wherein step (v) comprises a first stage in which the acid and the alkali metal methyl siliconate are metered simultaneously into the reaction medium at a pH of from 7.0 to 10.0, followed by a second stage in which the addition of the alkali metal methyl siliconate is stopped while the addition of the acid is continued and the pH of the reaction medium is lowered to below 6.

0.

9. 9. The method according to claim 7 or 8, wherein the at least one alkali metal methyl siliconate is sodium or potassium methyl siliconate.

10. A composition comprising a precipitated silica according to any one of claims 1 to 6 and at least one polymer.

11. An article comprising a precipitated silica according to any one of claims 1 to 6 or a composition according to claim 10.

12. 12. The article of claim 11 in the form of a shoe sole, a flooring, a gas barrier, a roller for a cableway, a seal for a household appliance, a seal for a liquid or gas pipe, a brake system seal, a pipe, a covering, a cable, an engine support, a battery separator, a conveyor belt, a transmission belt, a tire.

13. The article of claim 11 which is insulation, a resorcinol-formaldehyde / silica composite, concrete or paper.

14. A tyre or tyre element comprising a precipitated silica according to any one of claims 1 to 6 or a composition according to claim 10.

Citation Information

Patent Citations

  • Methods for producing silica, silica having specific pore dimensions and / or particle size distribution, and their use, particularly for polymer reinforcement.

    JP2005500238A

  • Use of pretreated precipitated silica as reinforcing filler for silicone elastomers and curable silicone elastomer compositions obtained by cold mixing

    JP2007519793A

  • Method for producing silica particle

    JP2015117138A

  • Method for producing modified precipitated silica and compositions containing modified precipitated silica

    JP2019514819A

  • Precipitated silica and process for its manufacture

    WO2018202752A1